Answer:
The simplified form of the given expression is [tex]10x^2 + 28x + 15[/tex]
Step-by-step explanation:
Here, the given expression is: [tex](2x^2+3)(4x+5)-8x(x^2-2)[/tex]
By Distributive Property:
A(B+C) = AB + AC
Now, expanding the given expression.
We get : [tex](2x^2+3)(4x+5)-8x(x^2-2) = 2x^2(4x+5) + 3(4x+5)- 8x(x^2) + 8x(2)\\=2x^2(4x) + 2x^2(5) + 3(4x) + 3(5) - 8x^3 +16x\\=8x^3 + 10x^2 + 12x + 15 - 8x^3 + 16x\\=10x^2 + 28x + 15[/tex]
Hence, the simplified form of the given expression is [tex]10x^2 + 28x + 15[/tex]